Ethnobotany, phytochemistry and neuropharmacological effects of Petiveria alliacea L. (Phytolaccaceae): A review. (5th June 2016) - Luz, Diandra Araújo; Pinheiro, Alana Miranda; Silva, Mallone Lopes; Monteiro, Marta Chagas; Prediger, Rui Daniel; Ferraz Maia, Cristiane Socorro; Fontes-Júnior, Enéas Andrade
Abstract: Ethnopharmacological relevance: Petiveria alliacea L. commonly grows in the tropical regions of the Americas such as the Amazon forest, Central America, Caribbean islands and Mexico, as well as specific regions of Africa. Popularly known by several different names including 'mucuracaá', 'guiné' and 'pipi', P. alliacea has been used in traditional medicine for the treatment of various central nervous system (CNS) disorders, such as anxiety, pain, memory deficits and seizures, as well as for its anaesthetic and sedative properties. Furthermore, the use of this species for religious ceremonies has been reported since the era of slavery in the Americas. Therefore, the present review aims to provide a critical and comprehensive overview of the ethnobotany, phytochemistry and pharmacological properties of P. alliacea, focusing on CNS pharmacological effects, in order to identify scientific lacunae and to open new perspectives for future research. Materials and methods: A literature search was performed on P. alliacea using ethnobotanical textbooks, published articles in peer-reviewed journals, unpublished materials, government survey reports and scientific databases such as PubMed, Scopus, Web of Science, Science Direct and Google Scholar. The Plant List, International Plant Name Index and Kew Botanical Garden Plant name databases were used to validate the scientific names. Results and discussion: Crude extracts, fractions and phytochemical constituents isolated from various parts of P. alliacea show a wide spectrum of neuropharmacological activities including anxiolytic, antidepressant, antinociceptive and anti-seizure, and as cognitive enhancers. Phytochemistry studies of P. alliacea indicate that this plant contains a diversity of biologically active compounds, with qualitative and quantitative variations of the major compounds depending on the region of collection and the harvest season, such as essential oil (Petiverina), saponinic glycosides, isoarborinol-triterpene, isoarborinol-acetate, isoarborinol-cinnamate, steroids, alkaloids, flavonoids and tannins. Root chemical analyses have revealed coumarins, benzyl-hydroxy-ethyl-trisulphide, benzaldehyde, benzoic acid, dibenzyl trisulphide, potassium nitrate, b-sitosterol, isoarborinol, isoarborinol-acetate, isoarborinol-cinnamate, polyphenols, trithiolaniacine, glucose and glycine. Conclusions: Many traditional uses of P. alliacea have now been validated by modern pharmacology research. The available data reviewed here support the emergence of P. alliacea as a potential source for the treatment of different CNS disorders including anxiety, depression, pain, epilepsy and memory impairments. However, further studies are certainly required to improve the knowledge about the mechanisms of action, toxicity and efficacy of the plant as well as about its bioactive compounds before it can be approved in terms of its safety for therapeutic applications. Graphical abstract: